2020
DOI: 10.1111/jdi.13309
|View full text |Cite
|
Sign up to set email alerts
|

SGLT2 inhibitors for genetic and acquired insulin resistance: Considerations for clinical use

Abstract: Administration of an sodium–glucose cotransporter 2 inhibitor to individuals with insulin resistance reduces the level of glucose disposal necessary to maintain glycemia as a result of the induced increase in urinary glucose excretion. The amount of insulin required for a certain level of glucose disposal, on which the evaluation of insulin resistance is usually based, might thus decrease even without amelioration of insulin resistance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 16 publications
0
11
0
Order By: Relevance
“…Recently, a trial showed benefits of long‐term treatment with metreleptin in persons with Rabson‐Mendenhall Syndrome 236 . Use of SGLT2i has also been reported to be beneficial in improving hyperglycemia 237,238 . For females, the hirsutism resulting from ovarian hyperandrogenism should be managed using similar strategies as for polycystic ovarian syndrome 239 …”
Section: Monogenic Insulin Resistance Syndromesmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, a trial showed benefits of long‐term treatment with metreleptin in persons with Rabson‐Mendenhall Syndrome 236 . Use of SGLT2i has also been reported to be beneficial in improving hyperglycemia 237,238 . For females, the hirsutism resulting from ovarian hyperandrogenism should be managed using similar strategies as for polycystic ovarian syndrome 239 …”
Section: Monogenic Insulin Resistance Syndromesmentioning
confidence: 99%
“… 236 Use of SGLT2i has also been reported to be beneficial in improving hyperglycemia. 237 , 238 For females, the hirsutism resulting from ovarian hyperandrogenism should be managed using similar strategies as for polycystic ovarian syndrome. 239 …”
Section: Monogenic Insulin Resistance Syndromesmentioning
confidence: 99%
“…His plasma blood ketone bodies had a variation of 0.1–0.7 mmol/L, but it was still far from the impending ketoacidosis limit (1.6–3.0 mmol/L) [6] during the treatment [6]. Previous reports of treatment with SGLT2 inhibitors in patients with severe insulin resistance syndromes were in cases of generalized lipodystrophy, SHORT syndrome, and type A insulin resistance syndrome [7, 8]. SGLT2 inhibitors, acting through an insulin-independent manner, are effective and safe in individuals with type 2 diabetes, and the report presented here demonstrated their effectiveness in a patient with RMS.…”
Section: Discussion/conclusionmentioning
confidence: 99%
“…Among these drugs, sodium-glucose transporter 2 (SGLT2) inhibitors have gained the stage because of their renoprotective effects [ 58 ], which are related to lowering of the intraglomerular pressure by modulation of pre- and post-glomerular vascular tone [ 59 ]. SGLT2 inhibitors lower blood glucose by increasing urinary glucose excretion with a mechanism that is apparently independent of insulin action [ 60 ]. While some studies have reported that surrogate indexes of insulin resistance such as the homeostasis model assessment (HOMA) and the Matsuda Index were improved by treatment of type 2 diabetes with SGLT2 inhibitors [ 60 ], studies conducted with the use of the hyperinsulinemic-euglycemic clamp provided controversial results [ 61 , 62 ].…”
Section: Insulin and The Kidneymentioning
confidence: 99%
“…SGLT2 inhibitors lower blood glucose by increasing urinary glucose excretion with a mechanism that is apparently independent of insulin action [ 60 ]. While some studies have reported that surrogate indexes of insulin resistance such as the homeostasis model assessment (HOMA) and the Matsuda Index were improved by treatment of type 2 diabetes with SGLT2 inhibitors [ 60 ], studies conducted with the use of the hyperinsulinemic-euglycemic clamp provided controversial results [ 61 , 62 ]. To date, only a few studies have specifically investigated the effects of SGLT2 inhibitors on renal responsiveness to insulin.…”
Section: Insulin and The Kidneymentioning
confidence: 99%